Generalized Method to Find the Generators of Matrix Algebras when its Dimension 2 and 3 - Ram Milan Singh (International Journal of Mathematics And its Applications, 2020)
Let A be an algebraically closed field of characteristic zero and consider a set of 2 × 2 or 3 × 3 matrices. Using a theorem of Shemesh, we give conditions for when the matrices in the set generate the full matrix algebra.